Grafting enhances drought tolerance by regulating and mobilizing proteome, transcriptome and molecular physiology in okra genotypes - Razi, Kaukab; Muneer, Sowbiya (Frontiers in Plant Science, 2023)
Drought stress poses a serious concern to the growth, development, and quality of the okra crop due to factors including decreased yield, inadequate development of dietary fibre, increased mite infestation, and decreased seed viability. Grafting is one of the strategies that have been developed to increase the drought stress tolerance of crops. We conducted proteomics, transcriptomics and integrated it with molecular physiology to assess the response of sensitive okra genotypes; NS7772 (G1), Green gold (G2) and OH3312 (G3) (scion) grafted to NS7774 (rootstock). In our studies we observed that sensitive okra genotypes grafted to tolerant genotypes mitigated the deleterious effects of drought stress through an increase in physiochemical parameters, and lowered reactive oxygen species. A comparative proteomic analysis showed a stress responsive proteins related to Photosynthesis, energy and metabolism, defence response, protein and nucleic acid biosynthesis. A proteomic investigation demonstrated that scions grafted onto okra rootstocks increased more photosynthesis-related proteins during drought stress, indicating an increase in photosynthetic activity when plants were subjected to drought stress. Furthermore, transcriptome of RD2, PP2C, HAT22, WRKY and DREB increased significantly, specifically for grafted NS7772 genotype. Furthermore, our study also indicated that grafting improved the yield components such as number of pods and seeds per plant, maximum fruit diameter, and maximum plant height in all genotypes which directly contributed towards their high resistance towards drought stress.